2003 CAG Educational Needs Assessment Report. (1st August 2003) - Leddin, Desmond; Daniels, Sandra; Sinclair, Paul
Abstract : The annual survey of Canadian Association of Gastroenterology (CAG) members' educational needs was conducted online this past April. One hundred eightyseven individuals (one fifth of the membership) completed the needs assessment. The topic most in demand for future educational events was inflammatory bowel disease, both from the clinical and basic science perspectives. Other highly rated topics were endoscopy, pharmacological therapeutics, celiac disease and pancreatitis/pancreatic disease. Educational materials were judged to be the most valuable component of exhibit areas. Results of the needs assessment were used to shape the 2004 Canadian Digestive Diseases Week (CDDW) program.